2014
DOI: 10.1002/dvdy.24215
|View full text |Cite
|
Sign up to set email alerts
|

FGF signaling is required for anterior but not posterior specification of the murine liver bud

Abstract: Background The definitive endoderm arises as a naive epithelial sheet that produces the entire gut tube and associated organs including the liver, pancreas and lungs. Murine explant studies demonstrate that Fibroblast Growth Factor (FGF) signaling from adjacent tissues is required to induce hepatic gene expression from isolated foregut endoderm. The requirement of FGF signaling during liver development is examined via small molecule inhibition during whole embryo culture. Results Loss of FGF signaling prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 62 publications
4
30
0
1
Order By: Relevance
“…The first is that the hepatic endoderm induction occurs differentially along the anterior/posterior axis. Posterior hepatoblast induction requires BMP signals, whereas anterior induction requires FGF signals . In agreement with this idea, we have demonstrated that the anterior and posterior hepatic endoderm is adjacent to distinct and potentially inductive mesoderm derivatives.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The first is that the hepatic endoderm induction occurs differentially along the anterior/posterior axis. Posterior hepatoblast induction requires BMP signals, whereas anterior induction requires FGF signals . In agreement with this idea, we have demonstrated that the anterior and posterior hepatic endoderm is adjacent to distinct and potentially inductive mesoderm derivatives.…”
Section: Discussionsupporting
confidence: 86%
“…We previously demonstrated that small molecule–mediated inhibition of FGF signaling leads to a selective loss of HNF4α in the anterior but not posterior liver bud of cultured embryos . Whereas E9.25 controls displayed pronouncedly thickened liver buds, loss of FGF signaling produced increased cell death throughout the bud and an abnormal thinning and loss of HNF4α in the anterior liver bud .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Kimberly Tremblay (University of Massachusetts, Amherst, USA) showed by fate mapping and laser ablation, that the lateral progenitors form the majority of the liver bud and require vascular endothelial growth factor (VEGF) for survival. By contrast, the medial progenitors contribute to the anterior bud and require fibroblast growth factor (FGF) signaling for specification (Wang et al, 2015b). It is unknown whether the progeny of these distinct progenitor populations produce functionally equivalent hepatic tissue.…”
Section: Endoderm Induction and Patterningmentioning
confidence: 99%